Resveratrol inhibits IL‐6‐induced ovarian cancer cell migration through epigenetic up‐regulation of autophagy. Issue 3 (3rd November 2016) - Ferraresi, Alessandra; Phadngam, Suratchanee; Morani, Federica; Galetto, Alessandra; Alabiso, Oscar; Chiorino, Giovanna; Isidoro, Ciro
Abstract : Interleukin‐6 (IL‐6), a pro‐inflammatory cytokine released by cancer‐associated fibroblasts, has been linked to the invasive and metastatic behavior of ovarian cancer cells. Resveratrol is a naturally occurring polyphenol with the potential to inhibit cancer cell migration. Here we show that Resveratrol and IL‐6 affect in an opposite manner the expression of RNA messengers and of microRNAs involved in cell locomotion and extracellular matrix remodeling associated with the invasive properties of ovarian cancer cells. Among the several potential candidates responsible for the anti‐invasive effect promoted by Resveratrol, here we focused our attention on ARH‐I ( DIRAS3 ), that encodes a Ras homolog GTPase of 26‐kDa. This protein is known to inhibit cell motility, and it has been shown to regulate autophagy by interacting with BECLIN 1. IL‐6 down‐regulated the expression of ARH‐I and inhibited the formation of LC3‐positive autophagic vacuoles, while promoting cell migration. On opposite, Resveratrol could counteract the IL‐6 induction of cell migration in ovarian cancer cells through induction of autophagy in the cells at the migration front, which was paralleled by up‐regulation of ARH‐I and down‐regulation of STAT3 expression. Spautin 1‐mediated disruption of BECLIN 1‐dependent autophagy abrogated the effects of Resveratrol, while promoting cell migration. The present data indicate that Resveratrol elicits its anti‐tumor effect through epigenetic mechanisms and support its inclusion in the chemotherapy regimen for highly aggressive ovarian cancers. © 2016 Wiley Periodicals, Inc.